Tourism planning and development in Crete: Recent tourism policies and their efficacy - Andriotis, Konstantinos (My University, 2001)
Focusing on the island of Crete, the study on which this paper is based recognises the importance of tourism for the economy. Due to extreme resource utilisation by mass tourism developments, insufficient planning and limited co-ordination and collaboration between the bodies involved in tourism activities, tourism can have a negative impact and conflicts may escalate. These conflicts are mainly related to the concentration of tourist arrivals in time and space, inappropriate use of resources, and limited incorporation of the community in the development and planning process. To offer solutions, various policies and strategies have been proposed/adopted at regional level. However, it is questionable whether the actions currently undertaken are efficient enough for the amelioration of tourism problems. A regional master plan is necessary in order to eliminate costs and ensure future balanced development.
Keywords: Environmental impact; Resource use; Tourism development; Tourism management